A Citation Study of LIS Dissertation in University Of Malaya for Collection Development - Yeap, C.K.; Kaur, K. (2007)
This study applies the citation analysis method to examine the use of information resources by postgraduate students of Master in Library and Information Science in preparing their dissertation at the University of Malaya. A sample of 40 MLIS thesis references from the period of 2000-2005 were examined for: year of publication; author; source title; bibliographic format; language; subject category; and place of publication. The core journal titles were compared with JCR listing and also availability at the University of Malaya library. The study shows that journals and books are still the most used sources for information and there is a steady increase in the use of electronic media by LIS researchers. Authorship pattern indicate preference for single authored works. This study serves as a baseline indicator of the use of resources by LIS researchers that can be used by librarians to focus their collection development to support research needs and a continuing assessment is deemed necessary because of the increasing availability of web or Internet resources.